2016
DOI: 10.1089/dna.2015.3118
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of CXCR4 Overexpressed Mesenchymal Stem Cells Augments Regeneration in Degenerated Intervertebral Discs

Abstract: SDF-1/CXCR4 chemotaxis signals play important roles in regulating the stem cell-based tissue regeneration. The aim of this research is to evaluate whether high expression of CXCR4 enhances the migration of mesenchymal stem cells (MSCs) and increases the efficiency of intervertebral disc (IVD) regeneration. MSCs overexpressing CXCR (CXCR4-MSC) were created by lentiviral-CXCR4-vect transfection, labeled with SPIO, and transplanted into rabbit degenerative IVD induced by annulus puncture. X-ray and T2-weighted MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Upon arrival at the injury site, BMSCs play an active role in attenuating liver injury, including significantly decreasing the size of the liver injury area, inhibiting liver cell apoptosis, and simultaneously promoting liver cell proliferation. These findings are accordance with previous reports of the positive effects of BMSCs in other pathological conditions 21 34 . Thus, from this study, we extended the scope of pathological conditions that could benefit from BMSCs transplanting therapy to LPS or sepsis-induced acute liver injury.…”
Section: Discussionsupporting
confidence: 93%
“…Upon arrival at the injury site, BMSCs play an active role in attenuating liver injury, including significantly decreasing the size of the liver injury area, inhibiting liver cell apoptosis, and simultaneously promoting liver cell proliferation. These findings are accordance with previous reports of the positive effects of BMSCs in other pathological conditions 21 34 . Thus, from this study, we extended the scope of pathological conditions that could benefit from BMSCs transplanting therapy to LPS or sepsis-induced acute liver injury.…”
Section: Discussionsupporting
confidence: 93%
“…For example, SDF-1 α has been shown to promote the survival of oligodendrocyte and trophoblast precursors [50, 51]. Wei et al [21] found that overexpression of CXCR4 could promote MSC retention in the degenerative IVD that enhanced the stem cell-based regeneration. In the present study, we also demonstrated that SDF-1 α could improve the late proliferation of NPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It was documented that the increased SDF-1 α in the osteoarthritis tissue could promote the recruitment of CXCR4-positive MSCs into the injured cartilage [18]. The expression of SDF-1 α was also reported to be upregulated in the human degenerative IVD [19, 20], and overexpression of its receptor CXCR4 could promote MSC retention in the degenerative IVD and enhance stem cell-based IVD regeneration [21]. In addition, the hyaluronan-based delivery of SDF-1 α significantly boosted the recruitment of MSCs into the degenerative IVD in an ex vivo organ culture [22].…”
Section: Introductionmentioning
confidence: 99%
“…These have potent chemotactic activity and their expression is upregulated in the degenerate IVD [59], moreover intradiscal administration of SDF-1/CXCR4 over-expressing stem cells promotes repair of degenerate IVDs [60]. SDF-1/CXCR4 mediated cell signalling promotes digit regeneration in mice a process driven by BMP-2 [61,62].…”
Section: Spine Research Issn 2471-8173mentioning
confidence: 99%